Application of x-ray CT to study diffusivity in cracked concrete through the observation of tracer transport - Darma, Ivan Sandi (Animo Repository, 2013)
This paper demonstrates the application of microfocus X-ray computed tomography (CT) to study solute transport in cracked concrete. Cracks in a cylindrical specimen of ordinary Portland cement (OPC) and fly ash mortar were induced using a splitting tensile test. Cesium Carbonate (Cs2CO 3) was then used as a tracer in the in-situ diffusion test with the aid of X-ray CT. Image analysis was also employed to measure the 3D crack geometry and tracer diffusivity from these CT images. The geometric tortuosity of the crack was approximately 1.25 irrespective of the crack opening width and whether fly ash was added or not. On the other hand, the constrictivity increased for the fly ash mortar having roughly the equivalent crack opening width. The measured diffusivity in the crack was controlled by both crack opening width and constrictivity. Results obtained from microtomographic images suggest that the entire crack space may not always be filled with the tracer. The diffusive transport of solute in cracks thus can be restricted from microstructure's point of view. Smaller crack opening would increase such restricted diffusion. Indications also suggest that the addition of fly ash would lead to the reduction of diffusivity through uncracked body of the mortar. Copyright © 2013 Japan Concrete Institute.